Consumer approach to food waste: evidences from a large scale survey in Italy - Falasconi, Luca; Cicatiello, Clara; Franco, Silvio; Segré, Andrea; Setti, Marco; Vittuari, Matteo; Cusano, Ilaria (Italian Review of Agricultural Economics, 2016)
In the EU 89 million tons of food are wasted every year, the largest fraction of which at the household level. Despite the key role of consumers in waste production, their approach to food waste has not been deeply analyzed so far. This paper aims at exploring the consumer attitude towards food waste, by analyzing the results of a survey held in two Italian cities in 2014, focused on the extent and reasons of the household food waste, and on consumers’ perception of effects and possible remedies to food waste. The results highlighted a general awareness of the effects of food waste, although the perception of such effects was more developed when they directly concerned the consumers. The main reasons of food waste declared by the respondents were the mismanagement of expiration dates, over-purchase, over-cooking, and a lack of knowledge about how to reuse the leftovers. A cluster analysis was conducted to identify consumer profiles with a similar approach to food waste. Such profiles were then analyzed across the two samples in order to check for possible overlapping, which could lead to a careful generalization of the results. Namely, we found 4 consumer profiles, named as “careful”, “virtuous”, “aware” and “unconcerned”, in both the samples analysed. Despite the many limitations of this very first analysis on household food waste, some interesting insights emerge, which might be usefully deepened in order to design effective strategies against food waste.